IMF Estimates of Potential Output Theory and Practice - De Masi, Paula (International Monetary Fund, 1997)
The concepts of potential output and the output gap are central to the IMF's analytical work in providing policy recommendations to member governments. This key role has stimulated research at the IMF to develop and refine estimation techniques. This paper summarizes the methodology and results of IMF research on potential output, which has focused mainly on the industrial countries but more recently has addressed issues related to developing countries and countries in transition. It then discusses the approaches that country desk officers use for operational purposes, and presents estimates of potential output for the major industrial countries